2010
DOI: 10.1007/s11033-010-0512-5
|View full text |Cite
|
Sign up to set email alerts
|

The Bcl I single nucleotide polymorphism of the human glucocorticoid receptor gene h-GR/NR3C1 promoter in patients with bronchial asthma: pilot study

Abstract: Bcl I in the promoter polymorphism observed within h-GR/NR3C1 gene may play an important role in the development of bronchial asthma and resistance to GCs in the severe bronchial asthma. The aim of the investigation was to study the correlation between this h-GR/NR3C1 gene polymorphism and occurrence of asthma in the population of Polish asthmatics. Peripheral blood was obtained from 70 healthy volunteers and 59 asthma patients. Structuralized anamnesis, spirometry and allergy skin prick tests were performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
3
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 32 publications
5
38
3
5
Order By: Relevance
“…rs6195, rs41423247) were associated with asthma [3,4]. Our results do not support the findings of these previous studies, specifically not those suggesting that a mutation (G/C) within rs41423247 in NR3C1 would have a protective effect on asthma development [4]. However, this association was shown in merely one study including only 59 adults with asthma and 70 healthy adults.…”
Section: To the Editorscontrasting
confidence: 99%
See 3 more Smart Citations
“…rs6195, rs41423247) were associated with asthma [3,4]. Our results do not support the findings of these previous studies, specifically not those suggesting that a mutation (G/C) within rs41423247 in NR3C1 would have a protective effect on asthma development [4]. However, this association was shown in merely one study including only 59 adults with asthma and 70 healthy adults.…”
Section: To the Editorscontrasting
confidence: 99%
“…However, this association was shown in merely one study including only 59 adults with asthma and 70 healthy adults. Since we found neither an association between rs41423247 and asthma in 1,434 adolescents (OR 0.99, 95% CI 0.76-1.28) nor in 998 adult individuals (OR 0.96, 95% CI 0.80-1.15), we feel that the findings from the study of PIETRAS et al [4] may be due to chance.…”
Section: To the Editorscontrasting
confidence: 58%
See 2 more Smart Citations
“…Depending on population, G-allele frequency of the polymorphism constitutes more than 30 %. Some investigations have proved the association of BclI polymorphism with body mass index (BMI) and abdominal obesity [10,11]; a few studies have shown its association with BA [12]. Still, no investigations related to the connection of BclI polymorphism with body mass index in BA patients were carried out.…”
Section: Introductionmentioning
confidence: 99%